IDENTIFIKASI KEMAMPUAN BERPIKIR KREATIF SISWA DENGAN METODE MIND MAPPING PADA PEMBELAJARAN FISIKA POKOK BAHASAN OPTIK DI SMA - Iriani Faizah Rofiqoh; Subiki Subiki; Aris Singgih Budiarso (JURNAL PEMBELAJARAN FISIKA, 2020)
Learning is a series of learning processes carried out by students to develop a student's knowledge, skill, and attitude. creativity is also required in the learning process. Creative thinking is the ability to solve problems in creating a success. one of the lessons that stressed creativity is the study of physic. Innovative learning can be done by selecting the methods of mind mapping presented in pitures and words. the mind mapping is the most effective and efficient way to input, store, and extract data from the brain. The study aims to identify student's creativite thinking ability by using the mind mapping method in Jember high school students. The study is a qualitative and qualitative deitique carried out at SMAN 4 Jember, SMAN Ambulu, and SMAN Jenggawah. Research tools involve the matter of creative thinking tests and the results of students sheets using the mind mapping method. Research shows that overall stages of the entire school being subjected to research, each indicator would be an average of 50-79. Within the criteria of a student's creativity can be categorized as moderate or creative enough. Keywords : Identification, creative thinking ability, mind mapping, optics